Essentials of contemporary business statistics - Williams, Thomas Arthur; Sweeney, Dennis J.; Anderson, David Ray (South-Western, Cengage Learning, 2012)
This textbooks provides a brief introduction to business statistics. The text balances a conceptual understanding of statistics with the real-world application of statistical methodology using problem-scenarios and real-world examples.